DIGITAL AND INFORMATION LITERACY SKILLS AS A BASE FOR UNIVERSITY-LEVEL SELF-REGULATED LEARNING - Wijayati, Primardiana Hermilia; Rizqiana, Nafila Ulfa; Bukhori, Herri Akhmad (Premise: Journal of English Education and Applied Linguistics, 2023)
A digital environment produces new concepts and understanding of language learning and teaching. Students are encouraged to be able to manage their goals and learning process independently. However, the success of self-regulated learning (SRL) in the digital era depends on the student's ability to explore the latest technology, which is defined as digital and information literacy. The problem comes when the use of higher technology unbalances students' digital and information literacy levels. Therefore, this research examined digital and information literacy skills as a base for ELF self-regulated learning. The researcher designed quantitative research. The questionnaires were distributed to 70 respondents from EFL students at the Department of English, Universitas Negeri Malang. Questionnaire data were analyzed using descriptive statistics to find digital literacy skills. The result showed that the students have a high level of digital literacy. There are underlying factors affecting their decisions and preferences that were explicated in the questionnaire responses, such as intake year, study load, and motivation. The findings about students' digital literacy can support teachers in planning interactive digital language learning. At the higher education level, there should be more practice and monitoring of collaborative learning activities.